The Firm Characteristics And Enterprise Risk Management Disclosures: Evidence From State-Owned Enterprise In Indonesia - Kurniawanto, Hudi (Archives of Business Research, 2021)
The purpose of this study is to examine the effect of firm characteristics on enterprise risk management disclosure. The object of research is State-Owned Enterprises listed on the Indonesia Stock Exchange in 2019-2020, a total sample of 40 annual reports using purposive sampling and multiple regression analysis. The results of this study prove that firm size and leverage do not affect enterprise risk management disclosure, while profitability affects enterprise risk management disclosure. The greater the profitability generated by the company, the wider the risk disclosure will be made to show stakeholders that State-Owned Enterprises in Indonesia can use capital efficiently.